A corpus-assisted discourse analysis of the representation of the 2017 Rohingya crisis in The Daily Star / Sharufatun Nahar - Sharufatun , Nahar (2020)
There is a noteworthy lack of research on media coverage of refugees and other minority groups in South Asia. The aim of this study is to examine the discursive construction of the 2017 Rohingya Crisis and the representation of key social actors in The Daily Star, a popular Bangladeshi newspaper. The corpus contains 406 online articles reporting the Rohingya issue, published on The Daily Star’s website from August 2017 to August 2018. A mixed method combining quantitative and qualitative techniques from Corpus Linguistics and Discourse Analysis is utilized to analyze the data. Using the corpus analysis software AntConc 3.5.8, collocations, clusters, and concordances of key terms are explored in order to identify prominent discourses. Simultaneously, textual analysis is carried out on extracts using van Leeuwen’s (1996, 2008) socio-semantic network model. This work is intended to enrich studies on refugee and migration issues, besides adding to existing literature on the Rohingya. Findings show that the Rohingya are predominantly portrayed as victims, followed by representation as problems and burdens in the host country. Myanmar is mostly represented as a savage and a violator of human rights. Bangladesh is represented as a savior to the Rohingya, while at the same time being depicted as being challenged by the Rohingya presence in the country. The Rohingya crisis is simultaneously constructed as a humanitarian issue and a securitarian one. Implications are discussed and avenues for further study are suggested.